Specific gravity of wood from two pines and its relation with edaphic properties - Vázquez-Cuecuecha, Oscar G.; Zamora-Campos, Eunise M.; García-Gallegos, Elizabeth; Ramírez-Flores, Juan Alberto (Instituto de Ecología, A.C., 2015)
The aim of this study was to identify wood density differences between sites for each species as well as to relate the basic wood density of Pinus patula and Pinus ayacahuite var. veitchii with some soil physico-chemical properties. In order to identify differences between wood density, soil properties and assess the influence degree of pH, percentage of organic matter, humic and non humic fractions, total carbon, texture, porosity and soil bulk density, two natural stands where both species coexist, were selected from Central Mexico. 78 trees were used to determine basic wood density. No differences within species between sites for basic wood density were found. Most of the edaphic properties were significantly different between sites and higher variation were observed within Ejido Ingenio del Rosario. Soil bulk density was negatively correlated with wood density of Pinus patula native from Ejido Ingenio del Rosario, Xico, Veracruz. It is concluded that soil factors do not influence strongly the expression of this feature in both species, so commercial or conservation plantations can be done in different soils types without changes in wood quality.